2021
DOI: 10.1155/2021/4922697
|View full text |Cite
|
Sign up to set email alerts
|

Green Internet of Things and Big Data Application in Smart Cities Development

Abstract: This study reveals that increases in the global population command an augmented demand for products and services that calls for more effective ways of using existing natural resources and materials. The recent development of information and communication technologies, which had a great impact on many areas, also had a damaging effect on the environment and human health. Therefore, societies are moving toward a greener future by reducing the consumption of nonrenewable materials, raw materials, and resources wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…To bridge the gap between Industry 4.0 and Society 5.0 in order to co-create value for the long-term sustainability of the ecosystem, some challenges still exist. For example, Yang et al, [27] and Bibri et al, [23] suggest using sensors to create data processing platforms and computing models in the context of sustainable smart cities of the future from the perspective of Society 5.0. In particular, an application of sensors is proposed by Francisco et al [25] and is aimed at the area of the energy efficiency of buildings.…”
Section: Motivation Of the Studymentioning
confidence: 99%
See 3 more Smart Citations
“…To bridge the gap between Industry 4.0 and Society 5.0 in order to co-create value for the long-term sustainability of the ecosystem, some challenges still exist. For example, Yang et al, [27] and Bibri et al, [23] suggest using sensors to create data processing platforms and computing models in the context of sustainable smart cities of the future from the perspective of Society 5.0. In particular, an application of sensors is proposed by Francisco et al [25] and is aimed at the area of the energy efficiency of buildings.…”
Section: Motivation Of the Studymentioning
confidence: 99%
“…These abilities turn simple objects into intelligent devices that can operate in real time [29,31], adapt to circumstances, and function without human intervention or supervision [59,62]. Sensors and intelligent actuators are already implemented [27] and give rise to a huge amount of data collection. The data collected must be stored, analyzed, and processed before being presented in a useful form.…”
Section: Conceptual Framework Of Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The development of the mobile network security environment is demonstrated in Figure 4. By the beginning of the 1970s, only phreaking and hacking attacks left telephone networks vulnerable, and technological progress dramatically occurred at present [34] and [35]. Telecommunications have demonstrated that an informatics program has changed dramatically.…”
Section: Mobile Network Protection and Vulnerability Environment Evol...mentioning
confidence: 99%